Peran Petani Jagung Dalam Meningkatkan Ekonomi Masyarakat Desa Margo Lestari - Badawi, Fuad; Astuti, Sri Yuli; Irawan, Hengki (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2024)
Maize farming has enormous potential in Margo Lestari Village. People see it as a promising way to generate income and improve their standard of living. This study aims to examine the role of maize farmers in improving the economy of Margo Lestari Village. The research method used is a field study by interviewing maize farmers and collecting data related to production, income, production costs, and the social and economic characteristics of farmers. The results show that maize cultivation contributes positively to farmers' income and regional economic growth. Income from maize cultivation increases along with the area of land cultivated, production generated, and production costs incurred. Factors such as education, experience, and women's participation also affect farmers' productivity and income. These findings are consistent with agricultural economic theory and previous research on the role of the agricultural sector in local economic growth. The policy implications of this study are the need for support for farmer education and training, as well as the promotion of women's participation in agriculture. These findings provide important insights into the contribution of the agricultural sector, particularly maize cultivation, in local economic development and form the basis for policies that support the growth of this sector.